Flash Card as a Media for Recognizing Symbol of Number in Early Childhood - Najiha Amalia; Raden Rachmi (PIAUD Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah, 2024)
The aim of the research is to introduce symbol of number through flash card because at the time of the initial research the kindergarten still uses simple learning methods and there are also some children who are less able to recognize numbers. This research uses a qualitative method by applying a case study approach, while data collection uses interviews, observation and documentation. Participants in this research are school principals, teachers and students. As for the research results, teachers must choose a theme that is in accordance with the learning plan that has been prepared, prepare and provide interesting media or learning materials, open up opportunities for children to play with flash card, repeat material from play activities using picture flash card, and evaluate activities